The hedonic price of pair trade coffee for the Italian consumer - Maietta O.W. (Food quality products in the advent of the 21st century: production, demand and public policy, 2005)
Consumers in developed countries are increasingly interested in the consumption of products incorporating ethical aspects, particularly fair trade products. They are usually distributed in a network of World Shops and more recently also introduced in supermarkets and shopping centres. The fair trade product with the highest share on the total is coffee. This study aims to ascertain the implicit price paid by Italian consumers for the fair trade content of coffee. The sample utilised is based on the purchase data of a representative sample of supermarket and shopping centre consumers observed from 1998 to 2002. Since scanner data are used, the analysis can allow for the numerous coffee attributes described by the labels: branded, organic, decaffeinated, fair trade, soluble, and so on. The empirical approach followed is the calculation of hedonic prices for the fair trade content and other attributes of coffee.
83. EAAE Seminar on Food Quality Products in the Advent of the 21st Century: Production, Demand and Public Policy, 2003/09/04-07, Chania (Greece)